Disposable flow cytometer with high efficiency in particle counting and sizing using an optofluidic lens - Song, Chaolong (2012)
Flow cytometers are widely applied to environmental monitoring, industrial testing, and biochemical studies. Integrating a flow cytometer into microfluidic networks helps to miniaturize the system and make it portable for field use. The integration of optical components, such as lenses, further improves the compactness and thus has been intensively studied recently. However, the current designs suffer from severe light scattering due to the roughness of the solid-based lens interface. In this Letter, we propose a flow cytometer using an optofluidic lens to focus the light beam. Benefiting from the smooth liquid–liquid lens interface and the refractive-index matching liquid as cladding streams, a light beam can be well focused without scattering. The variations of the signal peak values are reduced, owing to the small beam width at the beam waist. The device presents an efficient and accurate performance on both the counting and sizing of particles.